Organizational Commitment Mediates The Effect Of Work Ethic On Job Satisfaction At The Regional Office Of The Directorate General Of State Assets Of North Sumatra - Sabila Rambe, Salsa (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to determine the effect of work ethic on organizational commitment. To determine the effect of work ethic and organizational commitment on job satisfaction partially. To determine the effect of work ethic on job satisfaction through organizational commitment at the Regional Office of the Directorate General of State Assets of North Sumatra. The population in this study was 165 people and all of them were used as research samples. The sampling technique used was purposive sampling. The data analysis technique used was path analysis. The results of the study indicate that work ethic has a positive and significant effect on organizational commitment, work ethic has a positive and significant effect on job satisfaction, organizational commitment has a positive and insignificant effect on job satisfaction, organizational commitment does not mediate the effect of work ethic on job satisfaction at the Regional Office of the Directorate General of State Assets, North Sumatra.